Primary Vaginal Melanoma With Rhabdoid Features: A Case Report and Literature Review. (September 2017) - Lee, Chien-Kuan; Lin, Ho; Su, Chi-Feng; Kok, Victor C.
Abstract : Primary vaginal melanoma is a rare mucosal neoplasm, which is more aggressive than cutaneous melanoma. Information regarding its morphologic patterns is limited. In particular, the rhabdoid phenotype, mostly observed in metastatic or recurrent cutaneous melanomas, has yet to be reported at this anatomic location. Hence, a potential diagnostic difficulty may arise because of the inability to recognize this unusual histologic variant and its immunohistochemical aberrance. In this report, we describe the case of a primary vaginal melanoma in a 62-year-old woman, who exhibited both rhabdoid and small blue round cell morphologies, absence of S100 protein, and aberrant expression of desmin, CD56, and FLI-1. This report can facilitate the task of expanding the morphologic spectrum of vaginal melanoma, and prevent misdiagnosis and inadequate medical treatment.